Criteria of clinic diagnosis and effectiveness of biological therapy in viral hepatitis A - N. P. Тolokonskaya; Ye. N. Usolkina; N. I. Khokhlova; N. M. Vasilets (Бюллетень сибирской медицины)
The clinical trial of 60 patients (mean age (28.5 ± 0.9) years) with moderate severity hepatitis A (VHA) has been performed. The diagnosis in all patients was verified by detection of IgM to VHA by ELISA. In the course of the disease clinical symptoms and functional status of the liver were evaluated. We determined the activity of alanine transaminase, aspartate transaminase, gammaglutamyl transferase, alkaline phosphatase, and the content of bilirubin. Malondialdehyde (MDA) level in blood serum was determined as a laboratory indicator of endogenous intoxication. Main group consisted of 30 patients treated with antigomotoxic therapy, whereas in the control group (30 patients) the common therapy was carried out. A faster elimination of clinical and biochemical manifestations of the acute phase of VHA was established in the main group compared with the patients of the control group. In contrast to the latter, the average MDA in the main group patients 3 and 6 months after treatment did not differ significantly from the normal values.